Adipose retinol saturase is regulated by β-adrenergic signaling and its deletion impairs lipolysis in adipocytes and acute cold tolerance in mice - Chen Li; Marie F. Kiefer; Sarah Dittrich; Roberto E. Flores; Yueming Meng; Na Yang; Sascha Wulff; Sabrina Gohlke; Manuela Sommerfeld; Sylvia J. Wowro; Konstantin M. Petricek; Dominic Dürbeck; et al. (Elsevier, 2024)
Objective: Retinol saturase (RetSat) is an endoplasmic reticulum-localized oxidoreductase highly expressed in organs involved in lipid metabolism such as white (WAT) and brown adipose tissue (BAT). Cold exposure was shown to increase RETSAT protein in BAT but its relevance for non-shivering thermogenesis, a process with beneficial effects on metabolic health, is unknown. Methods: We analyzed the regulation of RetSat expression in white and brown adipocytes and different murine adipose tissue depots upon β-adrenergic stimulation and cold exposure. RetSat function during the differentiation and β-adrenergic stimulation of brown adipocytes was dissected by loss-of-function experiments. Mice with BAT-specific deletion of RetSat were generated and exposed to cold. Gene expression in human WAT was analyzed and the effect of RetSat depletion on adipocyte lipolysis investigated. Results: We show that cold exposure induces RetSat expression in both WAT and BAT of mice via β-adrenergic signaling. In brown adipocytes, RetSat has minor effects on differentiation but is required for maximal thermogenic gene and protein expression upon β-adrenergic stimulation and mitochondrial respiration. In mice, BAT-specific deletion of RetSat impaired acute but not long-term adaptation to cold exposure. RetSat expression in subcutaneous WAT of humans correlates with the expression of genes related to mitochondrial function. Mechanistically, we found that RetSat depletion impaired β-agonist-induced lipolysis, a major regulator of thermogenic gene expression in adipocytes. Conclusions: Thus, RetSat expression is under β-adrenergic control and determines thermogenic capacity of brown adipocytes and acute cold tolerance in mice. Modulating RetSat activity may allow for therapeutic interventions towards pathologies with inadequate metabolic activity.